The effect of carbon fabrics modification on the strength of carbon fiber reinforced plastic - Mustafa, L.M.; Yermakhanova, A.M.; Ismailov, M.B. (Kompleksnoe Ispolzovanie Mineralnogo Syra = Complex use of mineral resources, 2019)
This article reviews the study of influence of carbon fabrics modification on the strength of carbon fiber reinforced plastic. Two types of epoxy compound Etal Inject SLM of “cold curing” and Etal Inject-T of “heat curing”, nitric acid HNO3 of concentration 60 %, carbon fabric of Toho Tenax/Aksa 3k-1200-200 were used in the study. Comparisons of the strength properties of carbon plastic on these compounds were given. The best result was obtained on Etal Inject-T with tensile strength – 1000 MPa and in compression – 425 MPa. Carbon fabric modification was carried out by grafting carboxylated groups treated with HNO3 to the carbon fiber surface. The treatment time in acid varied from 0.5 to 6 minutes. The compressive strength by 17 % from 425 MPa to 497 MPa has been established to increase when carbon fiber by HNO3 is modified for from 0.5 min to 2 min, then the strength decreases enlarging the treatment time. The decrease in strength is associated with supersaturation of the surface of the fibers with carboxyl groups, which were destroyed during heat treatment. Thus, the surface oxidating of carbon fabric is the most effective method of increasing its adhesion to epoxy resin and the strength of carbon fiber. The functional groups formed during the oxidation process allow for a tight cross-linking of the epoxy matrix with carbon fiber. It was previously found that the strength of carbon fiber increases with the modification of epoxy resin with oxidized carbon nanotubes. An assumption is made about a uniform mechanism for strengthening carbon-fiber reinforced plastic due to chemically active functional groups, both on the surface of carbon fiber and on the surface of carbon nanotubes.